The Effect of the Use of Poster Media on Improving Literacy Ability of Grade IV Students of SDN Banjar Kemuning - Sittah Durrotun; Mohammad Setyo Wardhono (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
Literacy skills are an important element in encouraging the progress of the nation because it supports individual skills in various aspects of life. Literacy helps a person to understand, manage, and utilize information optimally. Currently, teachers are required to improve professionalism in developing students' basic literacy skills. However, low interest in reading and lack of literacy are one of the factors causing the low quality of education in Indonesia compared to other countries. This study aims to determine the influence of poster media on improving students' reading and writing literacy skills. The research uses a quantitative method with a pre-experimental design in the form of One Group Pretest-Posttest Design. The research sample is all students in grade IV of SDN Banjar Kemuning which totals 23 people. The results showed an increase in the average score from the pretest by 65.87 to 81.09 in the posttest. The paired sample t-test showed a significance value of 0.000 < 0.05, which means that there is a significant influence of the use of poster media on improving literacy skills. Poster media has been proven to be able to attract attention, increase participation, and help students understand information more effectively.